مظاهر تكريس الشفافية المالية في تسيير المؤسسات الإعلامية: Manifestations of Financial Transparency in the Management of Media Institutions - موساوي عبدالحليم (Journal of North African Economies, 2025)
The principle of transparency is closely related to media practice. Indeed, this principle is one of the most important restrictions imposed on freedom of the media, because the citizen has the right to know the funding sources of media institutions, be it through advertising or otherwise. Additionally, this funding must be subject to scrutiny by the bodies authorized to control Media activity, in order to guarantee the citizen's right to receive information away from bias and pressures, which means that this principle, before is both a protector of media freedom, and a guarantee for the citizen to obtain his right to truthful media. In this study, we will attempt to refer to the mechanisms devoted to establish aspects of this transparency in the management of media institutions. Practically, the influence of the media on those who control them is an established truth, whether they own or finance them in the form of support or advertising. This would disturb the credibility and the objectivity of the presented media material. In other words, the control of money over media institutions transforms the media sector from influential and independent, to influenced or affiliated. .